Keanekaragaman dan fungsi vegetasi di jalur hijau Kelurahan Kotabaru, Kecamatan Gondokusuman, Kota Yogyakarta - Firdausi, Eyda; Setyawan, Ahmad Dwi (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2025)
The development of urban areas needs to be accompanied by an improvement to the quality and quantity of the environment by providing public green open spaces such as green belt roads. This study aims to determine the diversity of vegetation and the functions in the green belt of Kotabaru Village, Yogyakarta City. The research was conducted using survey method in 14 green lanes to identify the type and amount of vegetation during September - October 2023. Based on the results of the study, 1407 individuals were found from 49 plant species. The diversity index (H') in the range of 0.64 - 2.12 is in the low to medium category. The evenness index (E) in the range of 0.69 - 0.93 is in the medium to high category. The dominance index (C) ranged from 0.12 to 0.38, including in the low category in all types of habitus (herbaceous, shrubs, shrubs, trees, and epiphytes). Vegetation in the green belt in Kotabaru Village can provide ecological, social, and economic functions for the surrounding community but still needs optimization in other functions such as community education. In addition, maintenance of green spaces also needs to be considered in order to provide sustainable vegetation functions.